AL-HADIST DALAM BUDAYA KOMUNIKASI DAN INTERAKSI PENDIDIKAN ISLAM: KAJIAN PERSPEKTIF MUHADDIS - Syarifah, Syarifah; Damanhuri, Damanhuri (Kuttab: Jurnal Ilmu Pendidikan Islam, 2024)
This study evaluates the isnad (chain of transmission), matn (text), and fiqh (understanding) of hadiths Abu Dawud Number 4463 and Ahmad Number 17309, which address communication and consultation in Islam, emphasizing Islamic education. Effective communication and interaction are crucial both individually and collectively, such as in consultations. The research aims to assess the quality of these hadiths and understand their application in communication and interaction within consultations. The method used is textual analysis of the hadith, referencing relevant literature. The findings indicate that the isnad quality of Abu Dawud Number 4463 requires further scrutiny regarding the discrepancy in the death years of Yahya bin Abi Bukair and Shaiban (bin Qarukh). However, Ahmad Number 17309 is considered sound and acceptable. The matn quality aligns with Islamic principles. The study concludes that consultation is a societal obligation in Islam, forming a fundamental basis for communication and social interaction, including in Islamic education. This research enhances understanding of hadith application in daily life and highlights the importance of consultation in Islam as a cornerstone in education and social interaction.